Analisis Kondisi Jalan dengan Metode PCI (Pavement Condition Index) (Studi Kasus: Ruas Jalan di Kota Kupang) - Hale Kore, Desri Marfenita; Djahamouw, Putri D K (Jurnal Kridatama Sains dan Teknologi, 2025)
Roads are connecting facilities made to facilitate transportation by land to support human movement and survival. Roads must be in good condition so that they can be used and passed by vehicles, but in reality, road conditions are not always in good condition due to damage - road damage due to the age of the road that has been long and also due to vehicle loads and other factors. Road damage that occurs in various regions is a very important problem. The damage can cause losses to users such as congestion due to increased travel time and also fatal accidents can occur. This road condition value will later be used as a reference for the preparation of a maintenance program that must be carried out. This research aims to find out the value of road conditions by first knowing the types of damage that exist and then calculating by the Pavement Condition Index (PCI) method. This research was conducted on road sections in Kupang City, namely Siliwangi - Garuda - Sumatra Street, H.R Koroh Street, Fetor Funay Street, Perintis Kemerdekaan Street, Veteran Street, Gor Flobamora Street, Amabi Tofa road and Taebenu road. The results obtained are the dominant types of damage to road sections in Kupang City are potholes, longitudinal/transverse cracks, crocodile cracks and aggregate release. The highest PCI value is 89 and the lowest is 19.4 with an average PCI value of 59.1, this shows that the condition of road sections in Kupang City is uneven, meaning that there are roads that are in very bad condition but there are roads that are still in good condition. To overcome the existing road damage, pothole filling, additional road surface coating, maintenance and reconstruction can be done